CT-guided percutaneous core needle biopsy of pulmonary nodules smaller than 2 cm: technical aspects and factors influencing accuracy - Juliano Ribeiro de Andrade; Rafael Dahmer Rocha; Priscila Mina Falsarella; Antonio Rahal Junior; Ricardo Sales dos Santos; Juliana Pereira Franceschini; Hiran Chrishantha Fernando; Rodrigo Gobbo Garcia (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To evaluate the diagnostic accuracy of CT-guided percutaneous core needle biopsy (CT-CNB) of pulmonary nodules ≤ 2 cm, as well as to identify factors influencing the accuracy of the procedure and its morbidity. Methods: This was a retrospective, single-center study of 170 consecutive patients undergoing CT-CNB of small pulmonary nodules (of ≤ 2 cm) between January of 2010 and August of 2015. Results: A total of 156 CT-CNBs yielded a definitive diagnosis, the overall diagnostic accuracy being 92.3%. Larger lesions were associated with a higher overall accuracy (OR = 1.30; p = 0.007). Parenchymal hemorrhage occurring during the procedure led to lower accuracy rates (OR = 0.13; p = 0.022). Pneumothorax was the most common complication. A pleura-to-lesion distance > 3 cm was identified as a risk factor for pneumothorax (OR = 16.94), whereas performing a blood patch after biopsy was a protective factor for pneumothorax (OR = 0.18). Conclusions: Small nodules (of < 2 cm) represent a technical challenge for diagnosis. CT-CNB is an excellent diagnostic tool, its accuracy being high.